2020
DOI: 10.1021/acsaem.0c01106
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Evaporation–Oxidation Deposited Aluminum Oxide as an Interfacial Modifier to Improve the Performance and Stability of Zinc Oxide-Based Planar Perovskite Solar Cells

Abstract: The acid−base chemistry at the interface of zinc oxide (ZnO) and methylammonium lead tri-iodide (perovskite) leads to a proton transfer reaction that results in perovskite degradation. In perovskite solar cells (PSCs), this reaction produces low efficiency and reduces the long-term stability. In this work, an aluminum (Al) layer of 1−2 nm thickness is thermally evaporated on top of ZnO or Al 3+ -doped ZnO (ZnO:Al) thin films and then annealed at 450 °C for 30 min. Thermal annealing converts the surface aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Ziran Ye et al reported Ag film on the liquid surface by using thermal evaporation technique for Surface Enhanced Raman scattering (SERS) application [44]. Hailin Hu et al fabricated Zinc oxide thin film by using this method for Planar Perovskite Solar Cell application [45]. Author group reported V 2 O 5 thin film supercapacitor prepared by thermal evaporation technique [46].…”
Section: Thermal Evaporationmentioning
confidence: 99%
“…Ziran Ye et al reported Ag film on the liquid surface by using thermal evaporation technique for Surface Enhanced Raman scattering (SERS) application [44]. Hailin Hu et al fabricated Zinc oxide thin film by using this method for Planar Perovskite Solar Cell application [45]. Author group reported V 2 O 5 thin film supercapacitor prepared by thermal evaporation technique [46].…”
Section: Thermal Evaporationmentioning
confidence: 99%
“…Por tal razón hemos incluido datos reales de celdas solares de perovskita híbrida fabricadas en nuestro laboratorio como parte de los indicadores a evaluar en el videojuego. Esto incluye más de cien recetas usadas en preparación de celdas solares, las cuales resultan en eficiencias variables (Arias-Ramos et al, 2020;Corpus-Mendoza et al, 2018;García-Cerrillo et al, 2017;Moreno-Romero et al, 2019;Rodríguez-Castañeda et al, 2020). De esta forma, el jugador es libre de fabricar celdas con la estructura de su preferencia y de experimentar múltiples parámetros de fabricación correlacionados a resultados experimentales reales para ofrecer un aprendizaje significativo.…”
Section: Diseño De Un Videojuegounclassified
“…However, the stability issue limits their practical application [ 11 ]. The presence of weak Pb-X bonds in PVT is the key factor for the degradation of the PVT layer under UV radiation, hot, and humid environments (X stands for Cl, Br, or I) [ 12 , 13 ]. The degradation of the PSCs can be alleviated via the formation of the high-quality PVT layer [ 14 ] as well as the selection of the charge transport layers.…”
Section: Introductionmentioning
confidence: 99%